Reimbursement Fraud di Era Digital: Tinjauan Sistematis Skema, Determinan, dan Kontrol Berbasis Risiko - Dwinanda, Rizky Ridho; Utama, Anak Agung Gde Satia (Universitas Negeri Padang, 2025)
This paper synthesizes contemporary evidence on reimbursement fraud across healthcare and adjacent claim-based systems, addressing four questions on dominant schemes, multi-level drivers, control effectiveness, and the digital evolution of modus operandi. Reimbursement fraud persists amid expanding automation, creating financial leakage, operational inefficiency, and credibility risks for payers and providers. The study’s novelty lies in integrating behavioral, organizational, and institutional lenses with a process-stage mapping that aligns “scheme × claim-stage × control,” while proposing a minimum reporting set for evaluation metrics beyond raw accuracy. A PRISMA-guided systematic review of Scopus-indexed, peer-reviewed articles (2016—2025) identifies thirteen studies and codes schemes, stages, determinants, interventions, and outcomes for narrative synthesis. Findings indicate recurrent upcoding, phantom billing, unbundling, duplicate claims, and cost inflation, concentrated at adjudication and post-payment review when verification is fragmented. Risk-based pre-authorization, targeted verification, and post-payment audits work best within interoperable data governance, complemented by ML/AI analytics, document forensics, and, where appropriate, blockchain for audit integrity. Digitalization scales fraudulent attempts, requiring continuous monitoring, model refresh, and shadow testing to manage drift and adaptive behavior. The main implication is a shift from tool-centric fixes to adaptive, risk-based systems of control that report accuracy, detection latency, false-positive burden, and financial recovery for policy-relevant decisions.